EVALUASI PENATAUSAHAAN BARANG MILIK DAERAH PADA PEMERINTAH KABUPATEN WAKATOBI - Dwi Wahyuniar; Andi Basru Wawo; Wa Ode Aswati (Accounting Student Series on Emerging Trends, 2026)
This study aims to evaluate the administration of regional property in Wakatobi Regency. This research uses a qualitative descriptive approach. Data collection methods are observation, interviews and documentation, researchers use qualitative data analysis techniques, namely data collection, data reduction, data presentation and conclusion drawing. The informants of this research were three (3) employees of the asset sector at the Regional Finance and Asset Agency of Wakatobi Regency. The results of this study indicate that the administration of regional milk goods at the Regional Finance and Asset Agency has not been carried out in accordance with Permendagri No. 19 of 2016 concerning Guidelines for the Management of Regional Property and Government Regulation No. 71 of 2010 concerning Government Accounting Standards, this is because the implementation related to inventory is still encountered obstacles, namely regional property that is no longer known to exist. As for reporting, it is also often late in reporting carried out by each OPD, this is due to the large number of regional property managed by these OPDs. There are also land assets that are still worth Rp.00 and do not have certificates. Problems with the administration of land fixed assets that exist at this time are caused by several factors, namely problems brought since the division with Buton Regency, grants from the community and the census of regional property has not been completed.